Методика розрахунку індукторів індукційних кухонних плит - Пантелят, Михайло Гаррійович; Гуренцов, Юрій Володимирович; Трофімов, Андрій Володимирович (НТУ "ХПІ", 2014)
В статті запропонована методика розрахунку індуктора – основного конструктивного елемента індукційної кухонної плити. Представлена в роботі методика розроблена на основі інженерних методів розрахунку плоских індукторів промислових індукційних нагрівачів з урахуванням особливостей та режимів роботи індукційних кухонних плит. Виконано розрахунки індукторів стосовно до ряду режимів нагрівання посуду різних геометричних розмірів. Проаналізовано отримані результати.

In the paper a technique for the calculation of inductor – main structural part of an induction cooker is proposed. The presented technique is developed on the base of engineering methods for calculation of industrial induction heaters’ planar inductors taking into account structural peculiarities and operation modes of induction cookers. Calculations of inductors regarding a number of heating modes for kitchen utensils of various sizes are carried out. Geometrical, electrical and power quantities such as outer and inner diameters of inductors, their thickness and number of turns, magnetic field strength on the utensils’ surface, current in the inductor, electrical efficiency, etc. are calculated. Obtained results are analyzed.
A technique for induction cookers’ inductors calculation
Keywords: індукційні плити; електропобутова техніка; індукційна кухонна плита; індуктор; induction cooker; inductor